Towards a crisis pre-emptive image management model - PANG, Augustine (Institutional Knowledge at Singapore Management University, 2012)
Purpose ‐ A good corporate image is important to organizations. However, little is elaborated on how organizations can work on their images. This study seeks to explicate the types of image management before, during, and after a crisis through the development of the crisis pre-emptive image management model. Design/methodology/approach ‐ Integrating insights from communication and marketing literature, this paper uses cases from the USA, Europe and Asia to make the concepts come alive. Findings ‐ At each stage of Wilcox and Cameron's crisis life cycle, different types of image management can take place. At the proactive stage are image creation and maintenance; at the strategic stage are image strengthening and transformation; at the reactive stage is image repair; and at the recovery stage are image renewal and reinvention. Research limitations/implications ‐ This paper is a comprehensive examination of the types of image management that organizations can consider as they seek to solidify their images at different stages of the organizations' existence. Practical implications ‐ This study demonstrates what organizations can do to communicate their desired images through multiple platforms with the aim of heightening their awareness of the profound effects lingering images have on the organization. Originality/value ‐ While certain concepts like image creation and maintenance and image repair have been explored before, this paper introduces new concepts like image strengthening, image transformation, image renewal, image reinvention, and enduring image with the view of demonstrating how image can work for or against the organization.